Sedimentary processes controlling ultralong cells of littoral transport: Placer formation and termination of the Orange sand highway in southern Angola. Issue 2 (27th July 2017) - Garzanti, Eduardo; Dinis, Pedro; Vermeesch, Pieter; Andò, Sergio; Hahn, Annette; Huvi, João; Limonta, Mara; Padoan, Marta; Resentini, Alberto; Rittner, Martin; Vezzoli, Giovanni
Abstract: This study focuses on the causes, modalities and obstacles of sediment transfer in the longest cell of littoral sand drift documented on Earth so far. Sand derived from the Orange River is dragged by swell waves and persistent southerly winds to accumulate in four successive dunefields in coastal Namibia to Angola. All four dunefields are terminated by river valleys, where aeolian sand is flushed back to the ocean; and yet sediment transport continues at sea, tracing an 1800 km long submarine sand highway. Sand drift would extend northward to beyond the Congo if the shelf did not become progressively narrower in southern Angola, where drifting sand is funnelled towards oceanic depths via canyon heads connected to river mouths. Garnet–magnetite placers are widespread along this coastal stretch, indicating systematic loss of the low‐density feldspatho‐quartzose fraction to the deep ocean. More than half of Moçamedes Desert sand is derived from the Orange River, and the rest in similar proportions from the Cunene River and from the Swakop and other rivers draining the Damara Orogen in Namibia. The Orange fingerprint, characterized by basaltic rock fragments, clinopyroxene grains and bimodal zircon‐age spectra with peaks at ca 0·5 Ga and ca 1·0 Ga, is lost abruptly at Namibe, and beach sands further north have abundant feldspar, amphibole‐epidote suites and unimodal zircon‐age spectra with a peak at ca 2·0 Ga, documenting local provenance from Palaeoproterozoic basement. Along with this oblique‐rifted continental margin, beach placers are dominated by Fe–Ti–Cr oxides with more monazite than garnet and thus have a geochemical signature sharply different from beach placers found all the way along the Orange littoral cell. High‐resolution mineralogical studies allow us to trace sediment dispersal over distances of thousands of kilometres, providing essential information for the correct reconstruction of 'source to sink' relationships in hydrocarbon exploration and to predict the long‐term impact of man‐made infrastructures on coastal sediment budgets.